An approach to some of the psychosocial and health effects of internet addiction by Algerian youth A field study in city of Constantine - Ghodban, Meriem; Naamoune, ABDESSALAM (Milev Journal of Research and Studies, 2019)
All users of the Internet suffer from many complications that may vary between psychological, social, mental, and physical health problems, especially those users who have been proven to be excessive use, and make them addicted to the use of the Internet according to the conditions set by many international studies, especially the standards of the table Clinical Diagnostic DSM4. Accordingly, this study came to reveal some of the psychological, social and physical effects resulting from the excessive use of the Internet among Algerian youth in a step to alert to the seriousness of the phenomenon, and the need to speed up treatment